Gemeente Malang: Keruangan, Segregasi, dan Potensi Wilayah 1914-1940 - Choirunnisak Nisa; Hendra Afiyanto (UIN Sunan Gunung Djati Bandung, 2022)
The reconstruction of the development of Colonial Cities in the Dutch East Indies which experienced growth and development after the issuance of the Sugar Law and Agrarian Law encourages the implementation of this study. After 1914, Malang City experienced development and changed its status to Gemeente based on Bouwplan I-VIII. During the Dutch colonial, this city functioned as a resort city, comfortable residence, and tourist area. The presence of colonial government changed the regional typology of Javanese and Islamic characteristics that already existed in this city. The division of the area was based on ethnicity according to the existing social status. The existence of urban development and the division of the city also applies to the economic facilities of each region.This study aims to describe the development of Malang City which leads to the separation of each ethnic area and affects the potential of the economic area. This study used a historical method with the stages of heuristics, criticism, interpretation, and historiography. This paper provided some findings. First, the development of Malang City during the colonial period resulted in Bouwplan I-VIII. Second, the prevailing typology of Java and Islam turned into the interests of the Colonial Government. Third, the results of urban development affect the economic value of each area or building.